Le régime juridique des mines du domaine public à Rome - Claude Domergue (Mélanges de la Casa de Velázquez, 2004)
The legal regime of the metalla publica in Rome has produced rivers of ink. In a recent book, A. Mateo addresses the root of the problem anew and produces a precise and coherent viewpoint. This article highlights and discusses the strong points of the argumentation, particularly regarding the role of the publicani and the regime introduced by the laws of Vipasca.